Sukuk Characteristics and Financial Performance Among Top 100 Listed Companies in Malaysia - Noor Arzmyra Hazrin; Aliana Shazma Amir; Siti Nor Junita Mohd Radzi (Jurnal Ilmiah Akuntansi Keuangan dan Bisnis (JIKABI), 2022)
This study examines the relationship between sukuk characteristics and financial performance by top 100 Malaysian public listed companies. The study uses 100 firm-year observations drawn from the population of non-financial companies in 2021. To achieve the objectives of this study, quantitative method of analysis is employed. Agency theory supports the application of several governance strategies to control "agents'" behaviour in organizations Thus, new financial instrument called sukuk has given rise to several concerns. Using multiple regression analysis, the results reveal that sukuk issuance and sukuk ratings have a positive significant impact on financial performance. The findings imply that the fact that the incentives for sukuk rely on the project's income or profit is another significant way they vary from traditional bonds. Additionally, the higher rated sukuk or known as investment grade sukuk, the safer and stable investment by the sukuk holders which may enhance financial performance. The present study is unique as it helps the researcher and others to explore the practice and prospect of sukuk market in Malaysia. Exploring new practice of sukuk in Malaysia will help to understand the importance of invest in sukuk as it can lower the risk of the company’s portfolio.